2009
DOI: 10.1111/j.1365-2672.2009.04284.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the growth performance of white shrimp,Litopenaeus vannamei, by a protease-producing probiotic,Bacillus subtilisE20, from natto

Abstract: Aims: To isolate and identify a benefic bacterium, Bacillus subtilis E20, from natto (fermented soybeans), and incorporate it into shrimp feed to promote shrimp growth performance. Methods and Results: A protease-producing bacterium, E20, isolated from natto was identified as B. subtilis by an API 50 CHB kit and the 16S rDNA sequence. B. subtilis E20 was able to grow at a broad range of temperatures (10-50°C), pH values (5-10), and NaCl levels (0-9%). The best culture conditions for B. subtilis E20 to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
158
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 33 publications
4
158
0
3
Order By: Relevance
“…Average daily growth (ADG) was high in S. cerevisiae (0.106±0.002 g) and B. subtilis (0.104 ± 0.002 g) followed by other strains such as Sb (0.092 ± 0.002 g), Lc (0.083 ± 0.001 g), Lr (0.082 ± 0.001 g), Ent (0.065 ± 0.004) and Cp (0.064 ± 0.002 g) whereas in control it was observed to be the lowest (0.062 ± 0.004 g). Similar to our findings, several studies have demonstrated the beneficial effects of probiotics on the growth performance in shrimp (Wang et al, 2007;Shen et al, 2010;Liu et al, 2009). …”
Section: Evaluation Of Probiotics In Penaeus Vannameisupporting
confidence: 92%
“…Average daily growth (ADG) was high in S. cerevisiae (0.106±0.002 g) and B. subtilis (0.104 ± 0.002 g) followed by other strains such as Sb (0.092 ± 0.002 g), Lc (0.083 ± 0.001 g), Lr (0.082 ± 0.001 g), Ent (0.065 ± 0.004) and Cp (0.064 ± 0.002 g) whereas in control it was observed to be the lowest (0.062 ± 0.004 g). Similar to our findings, several studies have demonstrated the beneficial effects of probiotics on the growth performance in shrimp (Wang et al, 2007;Shen et al, 2010;Liu et al, 2009). …”
Section: Evaluation Of Probiotics In Penaeus Vannameisupporting
confidence: 92%
“…Liu et al (2012) who showed that B. subtilis supplemented diet significantly higher growth than that of grouper fed the control diet after 28 days of feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Energy difference resulting from this process can be used for the growth. Liu et al (2009) mentioned that the increasing growth rate of aquatic organisms provided with probiotic in their feed was related to higher enzymatic digestion activity together with vitamin synthesis, therefore, digestibility and organism weight were also increased.…”
Section: Discussionmentioning
confidence: 99%